Assessing nutrient budgets and environmental impacts of coastal land-based aquaculture system in southeastern China - Kam Tang (Agriculture, Ecosystems & Environment, 2021)
Aquaculture can cause serious environmental pollution in the coastal zone. The construction of nutrient budget can provide a scientific basis for understanding the fate of nutrients in the aquaculture systems to facilitate sustainable aquaculture management. In this study, we characterized the nitrogen (N) and phosphorus (P) budgets of coastal land-based aquaculture ponds practicing monoculture of whiteleg shrimps (Litopenaeus vannamei) at the subtropical estuarine zone in southeastern China. Our results showed that commercial feed was the main input of both N (> 90%) and P (> 95%) during the farming period. N output was mainly through biomass harvesting (43–49 %) and sedimentation (28–44 %), with N2O emission only representing a small fraction of total N loss (≤ 0.03%). Similarly, most of the P was lost through sedimentation (56–68 %) and biomass harvesting (27–31 %). Despite the relatively high nutrient utilization efficiencies of the shrimp ponds, annual drainage of the ponds discharged 49.4 tons of N and 4.7 tons of P into the Min River Estuary, posing a serious threat to water quality. Based on the measured N2O emissions in this study, coastal shrimp ponds in China were estimated to release ca. 1.2 Gg N2O yr-1 to the atmosphere, contributing to 2.9% of the global aquaculture N2O emission. We found that approximately 10% of our nutrient budgets remained unresolved, which might be related to volatilization, seepage and periphyton growth. Better feed formulation, optimized feeding practice and effective sediment management are suggested to help minimize the environmental impacts of the fast-expanding shrimp aquaculture sector in China. Future studies should compare N2O emissions among aquaculture systems with different nutrient utilization efficiencies to improve our assessment of the overall climatic impact of aquaculture operations.